2005
DOI: 10.1093/icc/dth081
|View full text |Cite
|
Sign up to set email alerts
|

A matter of life and death: innovation and firm survival

Abstract: This paper examines the effects of innovation on the survival of manufacturing firms in the Netherlands. The demographics of firms according to their innovative performance and type of innovation are traced by using the Business Register population of all firms active in the Netherlands and the Community Innovation Survey. Through estimation of a parametric duration model, we observe that firms do benefit of an innovation premium that extends their life expectancy, independent of firm-specific traits such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
225
4
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(249 citation statements)
references
References 46 publications
12
225
4
8
Order By: Relevance
“…However, this is a first indication that innovation might not support growth and survival of firms in a transition economy. This stands in contrast to the usual empirical results estimated for firms in non-transition countries (Hall, 1987, Cefis andMarsili, 2006). We are not aware of a study that directly compares non-transition and transition countries.…”
contrasting
confidence: 76%
“…However, this is a first indication that innovation might not support growth and survival of firms in a transition economy. This stands in contrast to the usual empirical results estimated for firms in non-transition countries (Hall, 1987, Cefis andMarsili, 2006). We are not aware of a study that directly compares non-transition and transition countries.…”
contrasting
confidence: 76%
“…Research considering the particular characteristics of industries have suggested a number of influences that are often interrelated: the level of competition, clustering, stage of industry cycle, technological intensiveness, barriers to entry, as well as demand conditions and a minimum efficient scale (Cefis and Marsili 2005;Fritsch, Brixy, and Falck 2006;Helmers and Rogers 2008;Wennberg and Lindqvist 2010;Raspe and van Oort 2011). In terms of competition, where entry and exit costs are higher and involve a greater sunk component, the probability of failure is reduced (Helmers and Rogers 2008;Fotopoulos and Louri 2000).…”
Section: Please Insert Figure 2 About Herementioning
confidence: 99%
“…Some researchers (Mata et al, 1995) argue that, in some sectors, new firms have a greater capacity to find a place in the market and remain there. In short, the rate of survival appears to be linked with the level of technology of each sector, so that firms involved in activities that are more innovation intensive are in a better position to maintain their market position over time (Cefis and Marsili, 2005).…”
Section: Technology-based Firms and Survivalmentioning
confidence: 99%